Antecedents and Consequences of Employee Engagement in the Digital Era - Akimas , Hari Nugroho; Claudia, Meiske (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study intends to be a model of employee engagement in the digital era. The term